Análise das reflexões sobre a formação continuada para professores dos anos iniciais à luz da Lei 10.639/03 no período de 2015 a 2020 - Felipe, Joice Helena Adriano Marcello (2024)
The research aims to analyze the reflections that emerged about the continuing education actions of a group of Early Years teachers regarding the Afro-Brazilian History and Culture Theme and its mandatory nature in the Official Curriculum of the Education Network of the State of São Paulo. In the period proposed by the research, the group of teachers ranged from five to six classroom directors, two specialists in Art and a hospital class teacher, who were in the middle to the end of their teaching career. Federal Law nº 10.639/03 amended Law No. 9394/96 (Education Guidelines and Bases Law) by including the mandatory subject of Afro Brazilian History and Culture in the official curriculum of the Education Network. The research considers the designation of the role of the Pedagogical Coordinator, which is occupied by an effective teacher or category F, as an agent of continuing education for the implementation of Law nº 10.639/03. The role of pedagogical coordination, among other functions, is to promote the reflective practice of teachers that occurs individually and collectively during the training process. In these trainings, we sought to present African Culture and people of African descent as participants in the formation of Brazilian society, valuing diversity through cultural identity. This is qualitative research that had as instruments the analysis of documents, the bibliographical survey and the semi-structured questionnaire answered by six of the teachers who passed through the school unit in the period from 2015 to 2020. The path taken by the organization of the empirical material presents three cycles. I define it this way because its etymology resembles the concept of Sankofa (Carmo, 2016), a traditional proverb among the Akan-speaking peoples of West Africa, Ghana, Côte d’Ivoire, and Togo that teaches the possibility of going back to the roots, to be able to move forward. The first cycle narrates the reasons that led to the development of the first action that is represented in the development of the project on Africanity’s. The second cycle is related to the second training action that involves the expansion of this first project in another School Unit covering students from the first to the fifth year of elementary school. The third and final cycle, considers the last training action that is due to the rotation of teachers in the School Unit and studies on the subject, there was a need for education from the teachers' perspective on ethnic-racial issues, since the process training aims to raise awareness of educational processes and practices within schools. The aim was to answer the following question: what reflections emerge about continuing education actions aimed at Early Years teachers considering Law nº 10.639/03? The research result indicates that the project was configured in three cycles which are interconnected, and the achievement of the result is related to the demands presented during the practice, thus producing educational material. The educational product "Educating the Look: Didactic unit for continuing education actions in light of Law 10.639/03", brings suggestions both for teacher training and for the development of educational projects through literature. A pedagogical tool that establishes reflections and dialogue about the anti-racist movement and its implementation considering Law nº 10.639/03.